Pharmacophore based synthesis of 3-chloroquinoxaline-2-carboxamides as serotonin(3) (5-HT3) receptor antagonist - Mahesh, R.; Perumal, R.V.; Pandi, P.V. (2004)
A series of 3-chloroquinoxaline-2-carboxamides were designed and prepared by the condensation of 3-chloro-2-quinoxaloylchloride with appropriate Mannich bases of the p-aminophenol in the microwave environment. The synthesized compounds were evaluated for serotonin(3) (5-HT3) receptor antagonistic activities in longitudinal muscle-myenteric plexus (LMMP) preparation from guinea pig ileum against the 5-HT3 agonist, 2-methyl-5-HT. Compound 3g exhibited comparable 5-HT3 antagonistic activity (pA(2) 6.4) to that of standard antagonist Ondansetron (pA(2) 6.9), while the other compounds exhibited mild to moderate 5-HT3 antagonistic activities.